Formation of osteoclast-like cells on HA and TCP ceramics - Detsch, Rainer; et al. (Acta Biomaterialia, 2008)
An essential property of bone substitute materials is that they are integrated into the natural bone remodelling process, which involves the resorption by osteoclast cells and the formation by osteoblast cells. If monocyte cells adhere to a calcium phosphate surface (bone or bone substitute material), they can fuse together and form multinucleated osteoclast cells. In this study we show that osteoclast-like cells derived from a human leukoma monocytic lineage responded in a different way to tricalciumphosphate (TCP) than to hydroxyapatite (HA) ceramics. Both ceramics were degraded by resorbing cells; however, HA enhanced the formation of giant cells. The osteoclast-like cells on HA formed a more pronounced actin ring, and larger lacunas could be observed. TCP ceramics are medically used as bone substitute materials because of their high dissolution rate. On the other hand, highly soluble calcium phosphate ceramics like TCP seem to be inappropriate for osteoclast resorption because they produce a high calcium concentration in the osteoclast interface and in the environment. © 2007 Acta Materialia Inc.
Keywords: Bioresorption; Calcium phosphate; Degradation; Monocyte; Osteoclast